Слободата на говорот, медиумското изразување и правните норми - Донев, Дејан (Conrad-Adenauer-Stiftung, 2015)
Today the question of how to prevent the media to do what will comes to their mind is often. The answer to the posed question is ambiguous. Bearing in mind the liberal theory of social responsibility - which emphasizes the place and importance of freedom of the press as a place where the freedom of expression and the freedom of entrepreneurship is crossing, and further that the same freedom of press is outlined in the interest of the citizen, although essentially belongs to the press as an institution and as a media organization - control the media would mean a form of state intervention and reducing the pluralism of opinion. Then, how to achieve this intervention, while not to endanger the freedom of information? The answer to this question is the main intention of the author, i.e. the subject of research in this text.
Freedom of speech, media expression and juridical norms
Keywords: морална јавност, слобода на изразување, правна норма, морална норма